Sexual identity inequalities in the co-occurrence of poor mental health and health risk behaviours—a national cross-sectional study - Amal R. Khanolkar; Alexis Karamanos; Laia Becares (BMC Medicine)
Abstract Background Mental health problems (MHP, like depression/anxiety) and health and risk behaviours (HRBs) are more common among sexual minority adolescents (SMA) than in heterosexual peers. Limited studies have examined the co-occurrence of poor mental health and HRBs, if co-occurrence differs by sexual identity, and associated risks for self-harm and attempted suicide in adolescents. Methods This study included 10,233 adolescents aged 17 years (51% female/11% sexual minority) from the UK-wide Millennium Cohort Study. Sexual identity, MHP, seven HRBs (like regular smoking, drug use and sexual risk behaviour), self-harm and attempted suicide were self-reported. MHP were assessed using the strengths and difficulties questionnaire [SDQ] emotional symptoms subscale for depression/anxiety. We assessed associations between sexual identity and co-occurrence of MHP and HRBs using multinomial logistic regression. We estimated predicted probabilities for self-harm or attempted suicide based on sexual identity and MHP-HRB co-occurrence status using logistic regression models with appropriate interaction terms (between sexual identity and MHP-HRB co-occurrence status variables). Results MHP prevalence was higher in gay/lesbian (48%) and bisexual (49%) adolescents compared to heterosexual peers (19%). Self-harm (bisexual, 64%; gay/lesbian, 53%; heterosexual, 19%) and attempted suicide (bisexual, 24%; gay/lesbian, 17%; heterosexual, 6%) prevalence were higher in SMA compared to heterosexual peers. Gay/lesbian and bisexual adolescents consistently had higher probability for MHP-HRB co-occurrence compared to heterosexual peers (example, for gay/lesbian individuals: RRR 3.16 [95% CI 2.1–4.68] for MHP-1HRB, RRR 3.54 [95% CI 2.06–6.08] for MHP- ≥ 3HRB, for bisexual adolescents: RRR 2.44 [95% CI 1.85–3.20] for MHP-1HRB, RRR 4.11 [95% CI 2.99–5.66] for MHP- ≥ 3HRB). MHP-HRB co-occurrence and sexual minority identity were independently associated with greater odds for self-harm or attempted suicide. SMA had higher probabilities of reporting self-harm than heterosexual peers with the same level of MHP-HRB co-occurrence. For example, 37.2% of heterosexual adolescents with MHP-1HRB reported self-harm. Corresponding numbers were twice as high in bisexual (75.7%) and gay/lesbian (77.9%) individuals. Similarly, 58.3% of heterosexual adolescents with MHP- ≥ 3HRBs reported self-harm, increasing to 84.6% in bisexual and 83.8% in gay/lesbian peers. Conclusions SMA are more likely to experience MHP-HRB co-occurrence, which is associated with substantially higher risks for self-harm and attempted suicide compared to heterosexual peers. Findings highlight the need for better public health policies to address MHP and associated comorbidities to reduce sexual identity-related health inequities in adolescence.